Pemberdayaan Masyarakat Melalui Usaha Pembuatan Tempe di RT 03 RW 02 Kelurahan Koang Jaya Kecamatan Karawaci Kota Tangerang - Luluatul Fu’adah; Agus Suherman; Fitria Firdiyani (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Community empowerment is an effort to develop community independence and welfare through increasing knowledge, skills, behavior and abilities. According to data published by the Tangerang City Central Statistics Agency (BPS), the Tangerang City inflation rate has now reached 2.46%. The problem of unemployment in Tangerang City is an innovative strategy that creates small economic jobs and increases people's income. Like the tempeh business in Koang Jaya Village, Tangerang City. Therefore, community empowerment is a force to increase the income and economy of the small communities of Koang Jaya. The aim of this research is to determine community empowerment activities through the tempe business in Koang Jaya Village, Karawaci District, Tangerang City. Qualitative research methods were used in this research. Descriptive qualitative research method using observation, interviews and documentation. The results of this research show that the community empowerment process through the tempe making business in the Koang Jaya sub-district was carried out using Soeharto's theory (2011:50), namely planned and collective activities, improving people's lives, priorities for weak/disadvantaged groups through capacity building activities. The results of this research are that with community empowerment activities they can better ensure a clean economy by guiding the management of time, raw materials and other resources needed for tempeh production, not only that, but also ensuring that the tempeh is done well, with safety standards fulfilled. In this way, competition in the market will increase and have a positive impact on the local economy. With community empowerment activities, the economy of the Koang Jaya subdistrict community is improving more than before, so that their economic stability can be built through fostering management of time, raw materials and other resources needed in tempeh production.